2019
DOI: 10.33151/ajp.16.690
|View full text |Cite
|
Sign up to set email alerts
|

Basic Dimensions of Resilient Coping in Paramedics and Dispatchers

Abstract: IntroductionParamedics and dispatchers are exposed to high levels of stress and consequent psychological injury. Resilience training enhances the capacity to cope with stress and be resilient. It is widely recommended that resilience training be customised to specific occupational groups, but there is no established method for achieving such customisation. Exploratory factor analysis was used to identify dimensions underlying resilient coping in paramedics and dispatchers. The objective was to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In cases where the interaction between self-compassion and service role was non-significant, we examined the main effect of self-compassion. Consistent with prior findings suggesting that self-compassion in first responders protects against mental health issues such as depression and promotes resilience (Bilsker et al 2019;Kaurin et al 2018), we observed that self-compassion protected against general psychological distress, post-traumatic stress, secondary traumatic stress, depersonalization, and emotional exhaustion. Additionally, we observed that self-compassion was related to greater resilience and life satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In cases where the interaction between self-compassion and service role was non-significant, we examined the main effect of self-compassion. Consistent with prior findings suggesting that self-compassion in first responders protects against mental health issues such as depression and promotes resilience (Bilsker et al 2019;Kaurin et al 2018), we observed that self-compassion protected against general psychological distress, post-traumatic stress, secondary traumatic stress, depersonalization, and emotional exhaustion. Additionally, we observed that self-compassion was related to greater resilience and life satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…Although prior studies suggested positive effects of self-compassion on mental health among members of the general population and helping professionals (MacBeth and Gumley 2012;Raab 2014;Zessin et al 2015), very few studies have been conducted among first responders. To date, only three published studies were conducted with first responders, two of which primarily focused on depression and resilience as outcomes (Bilsker et al 2019;Kaurin et al 2018), and the third did not directly assess the relationship between self-compassion and mental health (Beaumont et al 2016c). The present study confirmed the protective role of self-compassion for a broad array of mental health outcomes across a wide range of first responders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean scores of the pre- and post-training of the control group were 144.0 and 146.3, respectively, whereas the mean scores of the experimental group were 140.6 and 173.4, respectively ( p -value < 0.05) (Anderson et al , 2017). Therefore, providing formative education and training to paramedic students on how to take care of themselves and on the principles of health and well-being before attending emergency clinical placements may improve their resilience and subsequently enhancing the quality of care (Anderson et al , 2017; Bilsker et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that resilience -an individual's capacity to effectively manage stressful/adverse life events (10)(11)(12)(13)(14)(15) -is associated with wellbeing and that this association may be enhanced through appropriate interventions (16). However, the effectiveness of preventive/proactive programs that aim to educate EMTs/paramedics such as those that focus on building resilience to mitigate the effects of working in potentially traumatic and stressful environments are limited.…”
Section: Introductionmentioning
confidence: 99%